Pastoralists' perceptions on the impact of Rift valley fever disease following an outbreak in North Eastern Kenya - Mburu, Caroline M.; Bukachi, Salome A.; Bett, Bernard K. (Springer, 2022)
Rift Valley fever (RVF) is a zoonotic disease which leads to livestock losses and human fatalities, thus impoverishing pastoralists who largely depend on livestock for their livelihood. These losses lead to both short- and long-term effects that perpetuate poverty and disrupt family order and structure. We used qualitative methods to understand the lived experiences of pastoralists with RVF after a major outbreak in Kenya. Using narratives, we identified the social, economic and psychological effects of this disease, while focus group discussions helped us to understand the experiences of the pastoralists during and after an outbreak. The major impacts were deprivation and impoverishment, abrupt disruption to their way of life and family dynamics and mistrust of the formal healthcare system. The latter was related to the isolation of patients and the presence of foreign medical personnel in the area that fueled mistrust. Efforts need to be made by public health practitioners and policy-makers to enhance dialogue between clinicians and pastoralists and to come up with practical ways of improving local people’s livelihoods during and after an RVF epidemic.